Reliatyvistinė paveldosaugos samprata: prielaidos, principai, galimybės - Kulevičius, Salvijus (Lietuvos istorijos studijos, 2009)
The relativistic conception of the heritage protection phenomenon is actualized in this article – the motives of such viewing existence, its underlying theoretical principles are formulated, and some tendencies of modern theory of the heritage protection are criticized based upon it. The conclusions of comparative analyses of various social heritage protection concepts and practices, and the experience of the international heritage protection (UNESCO, ICOMOS, ICCROM), give preconditions for the existence of this conception. In the first case, the comparison of the European, USA, Japanese, and other examples states that there exist different, and sometimes incompatible and even contradictory interpretations of this conception. In the last decade of the 20th century, it was also realized in the international heritage protection: from the search for universal standards of the heritage protection, one came to the acknowledgment of its relativity. Its angular point is considered to be the Nara Document on Authenticity (1994). Unfortunately, the relativistic perspective is not sufficiently adopted in the theoretical plane of the heritage protection, and this, first of all, leads to some mistakes and failures. The most typical and vivid of them is the presentation of one society's conception, most often that of the European countries, as the whole of the heritage protection phenomenon. There still is the vital and progressive evaluation. Moreover, there dominate the researches oriented to generalization (and at the same time to the partial levelling), but not to the revelation of the concrete social conceptions of the heritage protection. This illustrates perfectly well one of the most popular matrixes (paradigmatic model) of the heritage protection research – critical analysis. Three underlying principles of the relativistic conception of the heritage protection are stated based upon the modern provision of the heritage protection practice – the principles of multiperspectiveness, conventionality, and equivalence. They respectively describe that the heritage protection is ideologically and practically expressed as a variety of conceptions, that these conceptions are determined by the lifestyle and needs of a concrete society, and that all conceptions are equally good and correct.